2020
DOI: 10.33899/mjn.2020.164623
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Women’s Knowledge Regarding Cholelithiasis Diseases in Duhok City

Abstract: Background and Amis: Gallstone disease is one of the most common worldwide biliary tract disease in which the both genetic and environmental factors have roles in its pathogenesis. shortage of knowledge on gallstone disease contributed to poor dealing with cholelithiasis patients. Thus, the main aims of this study to assess the women knowledge regarding the cholelithiasis disease. Method:A cross-sectional study was conducted on 60 inpatient of gallstone disease in Azadi and emergency teaching hospital in Duhok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although some studies have shown that the awareness among woman was poorer we however didn't note any such difference. 12 Similarly, age didn't play a significant difference in the awareness of the patients regarding the disease. Out of the 103 patients under the age of 40 years, 13 (12.62%) had good awareness while in the group of patients over the age of 40, 14 (14.43%) had good awareness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although some studies have shown that the awareness among woman was poorer we however didn't note any such difference. 12 Similarly, age didn't play a significant difference in the awareness of the patients regarding the disease. Out of the 103 patients under the age of 40 years, 13 (12.62%) had good awareness while in the group of patients over the age of 40, 14 (14.43%) had good awareness.…”
Section: Discussionmentioning
confidence: 98%
“…It is believed that there is a complex interplay between demographic, clinical, knowledge and behavioral factors that affect patients adherence. 10 Studies done in various parts of the world have shown that the awareness of patients of gallstones regarding their disease is poor [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Medical Science, 26, ms9e2026 (2022) 2 of 10 composition of bile where in cooperation hereditary and environmental factors play a role have role in this commonest biliary tract disease over the world (Al-Amedy et al, 2020). Gallstones considered the primary triggering factor for acute cholecystitis in 90% of cases.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…Table(2) shows that; of all studied sample, 88.7% know what gallstones is. 39.9% of participants reported positive history of gallstone personally or in a family member (16.6% in mothers, 11.3% in sisters, 9.2% in fathers and only 6.4% in brothers).Regarding knowledge of normal function of the bladder, 27.8% reported bile production, 27.8% reported store and concentrate bile, 11.2% break down large fat droplets into smaller droplets, and 6.8% secrete hormones that help digestion run smoothly.Presentation of gallstones was reported as abdominal pain by 76.6%, fever, 21.7%, pale skin 36.7%, jaundice 36.7%, fatigue 41.9%, MEDICAL SCIENCE l ANALYSIS ARTICLE Medical Science, 26, ms9e2026 (2022)…”
mentioning
confidence: 91%
“…Gallstones are considered one of the primary digestive system diseases affecting humans (Kadhim, 2020;Al-Amedy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%